Effect of out-of-plane alkyl group's position in dye-sensitized solar cell efficiency: a structure-property relationship utilizing indoline-based unsymmetrical squaraine dyes - Alagumalai, Ananthan; Fairoos, Munavvar M. K.; Vellimalai, Punitharasu; Sil, Manik Chandra; Nithyanandhan, Jayaraj (ACS Applied Materials & Interfaces, 2016)
Squaraine dyes are promising chromophores to harvest visible and near-infrared (NIR) photons. A series of indoline-based unsymmetrical squaraine (SQ) dyes that contain alkyl chains at sp(3) C- and N- atoms of indoline moieties with a carboxylic acid anchoring group were synthesized. The optical and electrochemical properties of the SQ dyes in solution were nearly identical as there was no change in the D-A-D SQ framework; however, remarkable changes with respect to the power conversion efficiencies (PCE) were observed depending upon the position of alkyl groups in the dye. Introduction of alkyl groups to the indoline unit that was away from anchoring unit were helped in more dye loading with controlled organization of dyes on surface, increased charge transfer resistance, long electron lifetime, and hence higher PCE than that of the corresponding isomer in which the alkyl groups funtionalized indoline unit contains the carboxylic acid anchoring group. Careful analysis of incident photon-to current conversion efficiency (IPCE) profiles indicated the presence of aggregated structure on the TiO2 surface that contributes to the charge injection in the presence of a coadsorbent. A dye-sensitized solar cell (DSSC) device made out of SQ5 was achieved an efficiency of 9.0%, with an open-circuit potential (V-oc) of 660 mV and short-circuit current density (J(sc)) of 19.82 mA/cm 2, under simulated AM 1.5G illumination (100 mW/cm(2)). The IPCE profile of SQ5 shows an onset near to 750 nm with a good quantum efficiency (>80%) in the range of 550-700 nm, indicating the importance of self-organization of dyes on the TiO2 surface for an efficient charge injection. This present investigation revealed the importance of position of alkyl groups in the squaraine-based dyes for the better PCE.

Orthogonally functionalized donor/acceptor homo- and heterodimeric dyes for dye-sensitized solar cells: an approach to introduce panchromaticity and control the charge recombination - Sil, Manik Chandra; Sudhakar, Vediappan; Kavungathodi, Munavvar Fairoos Mele; Punitharasu, Vellimalai; Nithyanandhan, Jayaraj (ACS Applied Materials & Interfaces, 2017)
Organic dyes possessing conjugated pi-framework forms closely packed monolayers on photoanode in dye-sensitized solar cell (DSSC), because of the limitation to control the orientation and the extend of intermolecular pi-pi interaction, self-aggregation of dyes leads to reduced cell performance. In this report, a series of homodimeric (D-1-D-1, and D-2,-D-2) and heterodimeric (D-1-D-2 and D-2-D-4) donor/acceptor (D/A) dyes containing spiroBiProDOT pi-spacer were designed and synthesized by utilizing Pd-catalyzed direct arylation reaction and correlates the device performance with monomeric dyes (D-1 and D-2). Both the thiophenes (pi-spacer) of spiroBiProDOT were functionalized with same or different donor groups which led to homodimeric and heterodimeric chromophores in a single sensitizer. The homodimeric spirodye D-1-D-1 showed higher power conversion efficiency (PCE), of 7.6% with a V-oc and J(sc) of 0.672 V and 16.16 mA/cm(2), respectively. On the other hand, the monomeric D-1 exhibited a PCE of 3.2% (V-oc of 0.64 V and J(sc) of 7.2 mA/cm(2)); which is lower by 2.4 fold compared to dimeric analogue. The spiro-unit 20 provides flexibility between the incorporated chromophores to orient on TiO2 due to four sp(3)-centers, which arrest the molecular motions after chemisorption. This study shows a new molecular approach to incorporate two chromophores in the dimeric dye possessing complementary absorption characteristics toward panchromatic absorption. The attenuated charge recombination at TiO2/Dye/redox couple interface in case of D-1-D-1, owing to better passivation of TiO2 surface, was elucidated through impedance analysis. The FT-IR spectrum of D,-D, adsorbed on TiO2 film indicated both the carboxylic units were involved in chemisorption which makes strong coupling between dye and TiO2.

Homo- and heterodimeric dyes for dye-sensitized solar cells: panchromatic light absorption and modulated open circuit potential - Sil, Manik Chandra; Sudhakar, Vediappan; Singh, Ambarish Kumar; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (ChemPlusChem, 2018)
The design of dyes for panchromatic light absorption has attracted much attention in the field of dye-sensitized solar cells (DSSCs). An approach to enhance panchromatic light absorption utilizes mixtures of complementary light-absorbing dyes as well as dyes with specific anchoring groups that facilitate interfacial charge transfer with TiO2. Dipole-dipole interactions between the dye molecules on the surface broaden the spectrum, which results in decreased DSSC device performance. However, controlled aggregation of dyes results in broadening the spectral profile along with enhanced photocurrent generation. To control the dye-dye interaction, dimeric dyes with different dipole lengths D-1-D-sq, D-sq-D(sq)were systematically designed and synthesized. The photophysical and electrochemical properties were evaluated and the E-HOMO and E-LUMO levels were determined; these energy levels determines the electron injection from E-LUMO of the dye to E-CB of TiO2 and regeneration of oxidized dye by the electrolyte, respectively. The absorption spectra of D-sq-D-sq, D-1-D-sq were broadened in solution compared to model dye D-sq; this indicates that the dye-dye interaction is prominent in solution. In D-1-D-sq excitation energy transfer between photoexcited D-1 and D-sq was explained by using Forster resonance energy transfer (FRET). The homodimeric dye showed a device performace of 2.8 % (V-oc 0.607, J(sc) 6.62 mA/cm(2), ff 69.3 %),whereas the heterodimeric dye D-1-D-sq showed a device performance of 3.9 % (V-oc 0.652 V, J(sc) 8.89 mA/cm(2), ff 68.8 %). The increased photocurrent for D-1-D(sq)is due to the panchromatic IPCE response compared to D-sq-D-sq. The increased V(oc)is due to the effective passivation of the TiO2 surface by the spirolinker, and the effective dipole moment that shifts the conduction band on TiO2. Hence, the open circuit potential, V-oc, for the devices prepared from D-sq, D-1-D-sq and D-sq-D(sq)were systematically modulated by controlling the intermolecular pi-pi and intramolecular dipole-dipole interactions of the dimeric dyes.

Effect and position of spiro-bipropylenedioxythiophene pi-spacer in donor-pi-spacer-acceptor dyes for dye-sensitized solar cell - Sil, Manik Chandra; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (Dyes and Pigments, 2019)
Improper orientation and self-assembly of dyes on TiO2 surface are the main disadvantages at the dye-TiO2 interface that governs both charge injection and dye regeneration processes. In this report, a series of homo spiro-dimeric donor-pi-spacer-acceptor (D-pi-A) dyes based on bithiophene and terthiophene spacers with two-anchoring group containing dyes, TT1, T1T, TT1T were designed and synthesized by Pd-catalyzed successive Suzuki coupling followed by direct arylation reactions. The position of branching centre in TT1 and T1T was systematically varied, where the spiro unit was placed near and away from the anchoring carboxylic acid unit, respectively. The dimeric spiro-dye T1T showed device performance, which is 1.6 fold higher than its structural isomeric analogue TT1, of 3.9% with a V-oc and J(sc) of 0.593 V and 9.09 mA/cm2, respectively, whereas for the isomeric analogue TT1 a device performance of 2.45% (V-oc of 0.568 V and J(sc) of 6.25 mA/cm2) under simulated 1 Sun (100 mW/cm2) condition. The improved Voc for the dye T1T compared to TT1 dye was ascribed to the dipole moment exerted by the dyes on TiO2 surface. Further the PCE of 4.16% (V-oc 0.589 V, J(sc) 9.79 mA/cm2 respectively) maximum was observed, when an extra thiophene unit was inserted in between the donor and pi-spacer in dye TT1T. The shifting the position of branching spiroBiProDOT pi-spacer makes an impact on the device performance by synergistically enhancing both Voc and Jsc.
Keywords: CDCA; D-pi-A Spiro dye; Dye aggregation; dye-sensitized solar cell; spiroBiProDOT spacer